Minat Siswa Terhadap Pembelajaran Permainan Bola Voli - Aldini, Vivi; Ramadi, Ramadi; Rahmatullah, Muhammad Imam (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2024)
Interest and interest in the sport of volleyball becomes a very attractive option in school. Volleyball is not only suitable for all ages but can also be enjoyed by all genders. The interest in volleyball is reflected in the natural inclination of a person interested in this game, which provides opportunities for each individual to explore and develop his skills. This research is quantitative descriptive research that aims to determine the interest and factors in learning volleyball games. The sample in this study was all class XI students at Al-Fityah IT High School Pekanbaru with a total of 58 students. The instrument used in this study is a questionnaire using a Likert scale and questionnaire data can be analyzed using a percentage formula. Based on the results of the research conducted, it turns out that the interest of class XI students of Al-Fityah Pekanbaru IT High School towards volleyball games is quite high, reaching 50% or equivalent to half of the total class XI students of Al Fityah IT High School. In addition, it was found that internal factors influencing interest in the game of volleyball were also at a high level, reaching 56.9%. Meanwhile, student interest based on external factors is also included in the high category, which is 48.3%.